Software Architecture Superstream. (O'Reilly Media, Inc., 2022)
Developers and architects like to solve technical problems, not people problems. However, as Gerald Weinberg was famous for saying, "No matter what they tell you, it's always a people problem." Exceptional interpersonal skills--teamwork, facilitation, and leadership among them--are at least half of what it takes to become an effective software architect (regardless of the actual role or title an architect may have). But attaining the skills that will ensure you can communicate clearly and get stakeholder buy-in can be a difficult proposition. Join us to learn more about these essential skills, understand why they're so critical, and see how you can start putting them into practice. About the Software Architecture Superstream Series: This five-part series of half-day online events focuses on the hottest topics in software architecture, giving you the insights to keep pace with what's next while still accommodating legacy needs. Both seasoned software architects and those looking to break into the field will learn new skills and the latest information on the tools and technologies they need to succeed. What you'll learn and how you can apply it Understand how systems thinking can help you become a better developer and architect Learn how documentation can help you work better on asynchronous teams Discover how to get better at making complicated technical decisions This recording of a live event is for you because... You're a senior-level developer who wants to make the move to architect. You're a practicing software architect who wants to hone your skills and learn new software architecture techniques and practices. You want to better understand how to apply systems thinking and learn techniques to make better technical decisions. Recommended follow-up: Listen to The Software Architect Elevator (audiobook) or read the book Read Fundamentals of Software Architecture (book) Watch Presentation Patterns (video) Take Software Architecture by Example (live online training course with Neal Ford and Mark Richards).